Understanding how, for whom and under what circumstances telecare can support independence in community-dwelling older adults: a realist review - Lauren Fothergill; Niall Hayes; Yvonne Latham; Jenny Hamilton; Saiqa Ahmed; Carol Holland (BMC Geriatrics)
Abstract Background There is substantial interest among policy makers in using telecare to support independence in older adults. However, research on how telecare can be most beneficial in promoting independence is limited. This realist review aimed to understand the contexts in which telecare can support independence and for whom, to aid older people in remaining at home. Methods This realist review is consistent with the RAMESES quality and reporting standards. We followed a five-step process to conduct the review: (1) locating existing theories and concepts, (2) searching for evidence (3), selecting data, (4) extracting data, and (5) synthesising data. We analysed 32 studies published between 2004 and 2023 to identify core mechanisms of how telecare may lead to positive or negative impacts in the form of context-mechanism-outcome (CMO) configurations. CMOs were grouped into overall domains and contributed to an overall programme theory of how telecare works. Results Four key domains across 12 CMO configurations were identified, which suggest how telecare can support older adults in living independently (1). Telecare services should support older adults’ goal of staying at home by providing reassurance of help in an emergency and aid in detecting age-related deterioration (2). Telecare that supports autonomy by enabling choice over technological resources may support self-reliance and control over one’s life, including choosing the level of monitoring, freedom to call for help if needed, and the ability to customise technology to suit needs (3). Telecare that enables connections to existing or new social networks may reduce loneliness and social isolation for those who lack social resources. Finally (4), telecare must integrate into everyday life by fitting people’s existing context, skills, resources, and identity. To improve telecare implementation, consideration must be given to these mechanisms; otherwise, interventions risk being abandoned or underutilised and, as a result, may not adequately support older adults to remain living at home safely, creating a false sense of security. Conclusions Assessments of an individual’s needs and preferences should be carried out to ensure that telecare enables autonomy, supports the goal of remaining at home, facilitates connections to social support, and promotes integration into everyday life. Study registration PROSPERO CRD42021292384.